Pusat Promosi Dan Investasi Rokan Hulu Dengan Pendekatan Arsitektur Rokan Iv Koto - Ahmad Hidayat; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Promotion and Investment center in Pekanbaru is a facility of Rokan Hulu goverment aims to promote and expose potential posses by the Rokan Hulu such as natural resources, tourism sector, tradition, history, as well as the potential for industry and mining, also provides potential information of the existing workforce. The center is aimed to attract and facilitate prospective investors to access information and potential investments without visit to the Rokan Hulu, in order to improve and enhance climate investment. In addition, apart Representative Office, the center also serves as a venue for events and gatherings of the apparatus of government and the envoys of Rokan Hulul. The Rokan IV Koto Architectural Approach has chosen because it is one of the architectural heritages which is in the Rokan Hulu. Research methods used include field data collection, studies, and empirical studies library. The results of this research are to design buildings competent in the field of promotion and Investment with the principles of the architecture of Rokan IV Koto with focus on the function on buildings in accordance of the times.Keywords: Promotion, investment, architecture, Rokan IV Koto